Cyclooxygenase-2 and Prostaglandin E2 are Associated with Middle Cerebral Artery Occlusion and Hemorrhage in Patients with Moyamoya Disease - Zhang, Jianjian; Xiong, Zhongwei; Wang, Sheng; He, Yue; Sun, Shoujia; Wu, Xiaolin; Wang, Long; Zhang, Huaqiu; You, Chao; Wang, Yu; Chen, Jincao (Current Neurovascular Research, 2016)
Some inflammatory proteins, such as cyclooxygenase (COX)-2 and prostaglandin (PG) E2 are hypothesized to be implicated in the development of moyamoya disease (MMD). However, the functional roles of COX-2/PGE2 in the pathogenesis of MMD remain elusive. In this study, tiny pieces of middle cerebral artery (MCA) and superficial temporal artery (STA) were surgically harvested from 18 adult MMD patients and 5 surgical control patients. The expression levels of COX-2 and microsomal prostaglandin E2 synthase-1 (mPGES-1) in the vascular walls were immunohistochemically detected. With additional 10 healthy controls, the plasma levels of PGE2 were also measured by enzyme-linked immunosorbent assay (ELISA). Obvious intimal thickening was observed in both STA and MCA of MMD patients, but not in the controls. However, the MCA had a thicker intima than the STA (P < 0.01). Although plasma concentrations of PGE2 had no differences among the MMD patients, surgical controls and healthy controls, MCA of most MMD patients (15/18, 83.3%) were stained positively for COX-2 and all patients for mPGES-1. Staining of both COX-2 and mPGES-1 was more abundant in the MCA of hemorrhagic patients than those in their ischemic counterparts (P = 0.001 and 0.029, respectively). The expression levels of COX-2 were positively correlated with those of mPGES-1 (r = 0.647, P = 0.004). Positive COX-2 and mPGES-1 expressions were detected neither in the MCA samples from the surgical controls nor in all STA specimens. Our findings indicate that COX-2/PGE2 may be associated with the MCA occlusion and the hemorrhagic stroke in patients with MMD.
Keywords: middle cerebral artery